(untitled) (Intent Research Scientific Journal, 2023)
In recent years, there has been an increase in the number of diseases caused by phytopathogens. These pathogens affect plants at different stages of their growth and agricultural production. Depending on weather conditions and the phytosanitary state of crops, the prevalence of diseases can reach 70-80% of the total plant population, and yields decrease in some cases by 80-98% [3] . Plants have innate cellular immunity, but specific phytopathogens are able to overcome it. The article presents a brief description of the types of nematodes, their impact on reducing the yield and quality of watermelon of the "Marmar" (Marble) variety. A comparative study of nematodofauna in the farms of the villages of "Juraboy Darkhan" and "Ozod Darkhon" of the Akdarya district of Samarkand region is carried out.